PREFERENSI KONSUMEN TERHADAP PRODUK RUMAH TALAS BOGOR - Dwi Agus Riyanto Yonda; Ernah Ernah (JURNAL AGRIBISNIS TERPADU, 2017)
Taro is a distinctive commodity from Bogor which can be processed into a food product that is lapis talas. Producers who sell the product is Rumah Talas. The more producers who sell this product makes Rumah Talas has several competitors in marketing their products. This is a matter for consumers to choose which products to buy. This study aims to determine the consumers’ characteristics of Rumah Talas and to know the consumers preferences of Rumah Talas product and which attributes that become the consumer preferences. This research used survey method and analyzed quantitatively. Data analysis techniques used chi-square analysis and based on rank orders method. The results showed that the consumer characteristics of Rumah Talas were male, with married status, aged 46 - 60, undergraduate S1, with employment status of civil servants / military, and monthly income of Rp. 5.000.000 - Rp. 10.000.000. Products favored by consumers are products with moderate prices, good taste, products with purple, soft texture, attractive packaging, and likes products that have famous brand. Based on the rank or order of interest attributes of Rumah Talas product, the order of interest from the first to the last is price, taste, texture, packaging, brand, and color.